ANALYSIS OF FACTORS AFFECTING INTEREST RATE IN INDONESIA - Ahmad Saifuddin (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
The interest rate is the cost of borrowing or the price paid for borrowed funds. The interest rate is one of the important aspects in the banking world. This study aims to examine the influence of factors related to interest rate fluctuations set by Bank Indonesia. To examine the factors that affect interest rates in the short and long term. By using the independent variables of inflation, exchange rate, and also the money supply M2. The study was conducted using the Error Correction Model (ECM) method and secondary data for the period from 2019 to 2021. The results showed that all independent variables affected in the short and long term.